A tuberculosis contact investigation involving a large number of contacts tested with interferon-gamma release assay at a nursing school: Kanagawa, Japan, 2012 - Tasaka, Masako; Shimamura, Tamae; Iwata, Mami; Toyozawa, Takahiro; Ota, Masaki (Western Pacific Surveillance and Response, 2018)
Objectives: In May 2012, a teacher of a nursing school with nearly 300 staff members and students in Japan was diagnosed with sputum smear-positive pulmonary tuberculosis (TB), leading to a large contact investigation involving nearly 300 contacts. Herein we describe the contacts’ closeness to the index TB patient and the positivity of interferon-gamma release assay (IGRA). Methods: TB was diagnosed when a person had samples that tested bacteriologically positive for TB, or was determined to have TB by a physician. A latent TB infection (LTBI) case was defined as one in which a person tested positive in IGRA. Results: A total of 288 persons were screened with IGRA; however, two were excluded because of histories of TB and LTBI treatment; thus 286 were analyzed. Eleven persons (3.8%, 95% confidence interval [95%CI]: 1.9-6.8) tested positive for IGRA. Of the 11, a third year student was found to have pulmonary TB disease by chest X-ray. The positivity in IGRA among close contact staff members (4 of 21, 19%, 95%CI: 5.4-42%) with a statistically significant relative risk of 17 (95%CI: 2.0-140) was high compared with that of the third year students (1 of 88, 1.1% [95%CI: 0.028-6.2]). The Cochran-Armitage test revealed a statistically significant trend in the risk of TB infection among the staff and students (close contact staff> 2nd year> 1st year> 3rd year students, p<0.0025). Discussion: The authors thus recommend that teachers should undergo health examinations, including regular chest X-ray examinations.